TRADISI NGADUDUKEUN PADA MASYARAKAT SUNDA WARUKAUM KABUPATEN BOGOR - Sopa, Sopa (JURNAL PENELITIAN KEISLAMAN, 2010)
Islam in Sunda has diverse local elements. One of them is ngadudukeun, a ritual performed to control rain. The ritual is conducted by Sundanese Warukaum living in Bogor regency that has the high rain volume. The study follows Geertzâs perspective on the interpretation of culture and aims to get a deep understanding of the meanings of this ritual tradition from the native point of view. The data were gathered through observation and interviews. This study reveals that the ngadudukeun ritual consists of three stages involving both local and religious practices. The first stage is called petungan or pitungan that uses local mantra of Ajisaka to figure out the right time or day for an event. The second and third is conducted during maleman mangkat and maleman rame led by religious leaders. The Sundanese in Bogor believe that the ritual has a fundamental base from the Islamic scriptures, the Qurâan and the Prophet Tradition. To them, the ritual thus does not deviate from religion because it is seen as a spiritual endeavor based on Islamic texts to sustain their physical efforts.